KREATIVITAS GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI KEJENUHAN SISWA DI SMP NEGERI 5 BANJARBARU KALIMANTAN SELATAN - Imaniah Elfa Rachmah (Program Studi PAI STAI Al Falah Banjarbaru, 2023)
Abstract: The purpose of this study was to describe how the Creativity of Islamic Religious Education Teachers overcomes the saturation of students at SMP Negeri 5 Banjarbaru, South Kalimantan, and describes what aspects support and hinder the creativity of Islamic Religious Education teachers in overcoming this saturation. The subjects in this study were 2 Islamic religious education teachers for class VII and class XI, 3 students for class VII, and 3 students for class IX at SMP Negeri 5 Banjarbaru as well as supporting and inhibiting aspects. Data collection techniques, using non-participant observation techniques, structured interviews, and documentation. Then the data is processed with Data Processing Techniques in the form of data classification, editing, and data interpretation. Then analyzed by qualitative descriptive analysis and inductively concluded. The results of the research on the Creativity of Islamic Religious Education Teachers in Overcoming the Saturation of Students at SMP Negeri 5 Banjarbaru show that PAI teachers at SMP Negeri 5 Banjarbaru are included in the category of creative teachers. The creativity in question can be known from; Teacher Creativity related to methods, Teacher Creativity related to the use of learning media, and Teacher Creativity related to student strengthening. Aspects supporting the creativity of Islamic Religious Education Teachers at SMP Negeri 5 Banjarbaru include; The internal aspect is the educational background of the PAI teacher, the teaching experience of the PAI teacher, the personality of the PAI teacher and the external aspect is the school's support and students' intrinsic motivation. Barriers to the creativity of Islamic Religious Education Teachers at SMP Negeri 5 Banjarbaru in the form of limited learning media tools, unstable network connections and parental supervision. Keywords: Islamic Religious Education Teachers, Learning Saturation, Teacher Creativity. Abstrak: Tujuan penelitian ini adalah untuk mendeskripsikan bagaimana Kreativitas Guru Pendidikan Agama Islam mengatasi kejenuhan siswa di SMP Negeri 5 Banjarbaru Kalimantan Selatan, serta mendeskripsikan aspek apa saja yang mendukung dan menghambat kreativitas guru Pendidikan Agama Islam dalam mengatasi kejenuhan tersebut. Subjek dalam penelitian ini adalah 2 orang guru pendidikan agama Islam untuk kelas VII dan kelas XI, 3 siswa untuk kelas VII, dan 3 siswa untuk kelas IX di SMP Negeri 5 Banjarbaru serta aspek pendukung dan penghambat. Teknik pengumpulan data, menggunakan teknik observasi non partisipan, wawancara terstruktur, dan dokumentasi. Kemudian data tersebut diolah dengan Teknik Pengolahan Data berupa klasifikasi data, editing, dan interpretasi data. Kemudian dianalisis dengan analisis deskriptif kualitatif dan ditarik kesimpulan secara induktif. Hasil penelitian Kreativitas Guru Pendidikan Agama Islam Dalam Mengatasi Kejenuhan Siswa SMP Negeri 5 Banjarbaru menunjukkan bahwa guru PAI SMP Negeri 5 Banjarbaru termasuk dalam kategori guru kreatif. Kreativitas yang dimaksud dapat diketahui dari; Kreativitas Guru terkait metode, Kreativitas Guru terkait penggunaan media pembelajaran, dan Kreativitas Guru terkait penguatan siswa. Aspek pendukung kreativitas Guru Pendidikan Agama Islam di SMP Negeri 5 Banjarbaru meliputi; Aspek internal adalah latar belakang pendidikan guru PAI, pengalaman mengajar guru PAI, kepribadian guru PAI dan aspek eksternal adalah dukungan sekolah dan motivasi intrinsik siswa. Hambatan kreativitas Guru Pendidikan Agama Islam SMP Negeri 5 Banjarbaru berupa keterbatasan alat media pembelajaran, koneksi jaringan yang tidak stabil dan pengawasan orang tua. Kata kunci: Guru Pendidikan Agama Islam, Kejenuhan Belajar, Kreativitas Guru.